Analisis Jejaring Sosial Berdasarkan Topik Perbincangan “PPN 12 Persen” Di Sosial Media X - Yudatama, I Ketut (Journal Informatics Nivedita, 2026)
The policy to increase the Value Added Tax (VAT) rate to 12%, as mandated by Law Number 7 of 2021 concerning the Harmonization of Tax Regulations, has sparked diverse responses from the public, particularly on X (formerly Twitter) as a digital public discourse space. This study aims to analyze the social network structure and identify central actors within the public conversation regarding the "PPN 12 Persen" (12 Percent VAT) issue on X. The methodology employs Social Network Analysis (SNA), utilizing Python and Selenium for web scraping, and Gephi software for network visualization and analysis. Data collected from October 2024 to March 2025 yielded 4,092 nodes and 3,799 edges characterized as a directed graph. The results indicate that the network has low density and is divided into numerous communities; however, it possesses a network diameter of 4 and an average path length of 1.38, suggesting relatively short distances between actors. Centrality analysis reveals that the account @prabowo is the most influential actor with the highest eigenvector centrality, signifying the dominance of a single primary actor within the network. Although the network is fragmented and centralized, information dissemination remains rapid within the established network structure.